Personnel Administration on the Saranee Dhamma 6 Principles of Educational Institution Administrators under Roi Et Primary Educational Service Area Office 1 - Anuphan, Pinya; Vichitpanyaphorn, Phrakhru (Journal of Graduate MCU KhonKaen Campus, 2023)
This research aims to 1) study personnel management according to the Saranee Dhamma 6 Principles of Educational Institution Administrators under Roi Et Primary Educational Service Area Office 1, 2) to compare personnel management according to the Saranee Dhamma 6 Principles of educational administrators, classified by position, education background, and work experience, and 3) to study the approach to personnel management according to the Saranee Dhamma 6 Principles of educational administrators among a sample group of 335 administrators and teachers. The research tools used are a questionnaire with an estimated reliability of 0.87, and an IOC value between 0.67-1.00, and statistical analysis tools including frequency, percentage, mean, standard deviation, independent t-test, and one-way ANOVA F-test. The results show that: 1) Personnel management in accordance with the 6 Principles is generally practiced to the highest level. The aspects ranked by average from highest to lowest are: development of civil service teachers and educational personnel, recruitment and appointment, plan on staff, management on salary increments, and job performance evaluation. 2) The results of comparing opinions on personnel management according to the 6 Principles of the Saranee Dhamma have no difference based on position and educational level, while there is a significant statistical difference in opinions based on work experience at a level of .05. 3) The guidelines for personnel management based on the 6 Principles of the Saranee Dhamma found 5 crucial necessities. First, workforce planning should prioritize implementation according to the plan. The structure and responsibilities of personnel should be clearly defined and appropriate for the educational institution. Second, recruitment and appointment should be determined by the educational qualifications, knowledge, and abilities that match the position without discrimination and with equality. Next, actions related to salary raises should have a salary review committee appointed by management to conduct transparent salary review meetings that can be verified by using an impartial method. Performance evaluations should be considered with fairness and impartiality, without any bias towards any individual within the organization. Ultimately, development of civil servants and educational personnel should be supported by funding for training.